MacroH2A1 histone variant represses rDNA transcription. Issue 1 (25th September 2013) - Cong, Rong; Das, Sadhan; Douet, Julien; Wong, Jiemin; Buschbeck, Marcus; Mongelard, Fabien; Bouvet, Philippe
Abstract: The regulation of ribosomal DNA transcription is an important step for the control of cell growth. Epigenetic marks such as DNA methylation and posttranslational modifications of canonical histones have been involved in this regulation, but much less is known about the role of histone variants. In this work, we show that the histone variant macroH2A1 is present on the promoter of methylated rDNA genes. The inhibition of the expression of macroH2A1 in human HeLa and HepG2 cells and in a mouse ES cell line resulted in an up to 5-fold increase of pre-rRNA levels. This increased accumulation of pre-rRNA is accompanied by an increase of the loading of RNA polymerase I and UBF on the rDNA without any changes in the number of active rDNA genes. The inhibition of RNA polymerase I transcription by actinomycin D or by knocking down nucleolin, induces the recruitment of macroH2A1 on the rDNA and the relocalization of macroH2A1 in the nucleolus. Interestingly, the inhibition of rDNA transcription induced by nucleolin depletion is alleviated by the inactivation of macroH2A1. These results demonstrate that macroH2A1 is a new factor involved in the regulation of rDNA transcription.